Wnt5A signaling supports antigen processing and CD8 T cell activation - Sarraf, Tresa Rani; Sen, Malini (Frontiers in Immunology, 2022)
Antigen processing and antigen-specific CD8 T cell activation form part and parcel of cell-mediated immunity to infections. Yet, several lacunae remain in our understanding of how antigen processing and CD8 T cell response are coordinated. In this study, using mouse bone marrow-derived dendritic cells (BMDC) as antigen-presenting cells and Ovalbumin (OVA)/DQ-Ovalbumin (DQ-OVA) as model antigen we demonstrated that Wnt5A signaling in BMDC supports antigen processing/presentation and concomitant CD8 T cell activation through regulation of actin and proteasome dynamics. Recombinant Wnt5A conditioning of BMDC and associated actin assembly facilitated DQ-OVA processing, which was inhibited by the proteasome inhibitor MG132. Moreover, Wnt5A depletion led to a significant reduction in OVA processing and presentation. Impaired DQ-OVA processing in Wnt5A depleted BMDC correlated with altered dynamics of both actin and the proteasome regulator PA28-PA28, and reduced association of DQ-OVA with actin and proteasome subunits. Inhibited OVA processing/presentation in the Wnt5A depleted BMDC also resulted in subdued activation of OVA-sensitized CD8 T cells in co-culture with the BMDC. In concurrence with these findings, we demonstrated reduced OVA processing and impaired CD8 T cell response to OVA immunization in Wnt5A heterozygous mice lacking a copy of the Wnt5A gene in comparison to the wild-type cohorts. Taken together, our results reveal a crucial requirement of Wnt5A signaling in antigen processing/presentation and CD8 T cell activation, thus unveiling a vital regulatory node of cell-mediated immunity, unidentified thus far.